Clinical management of pregnancy in women with Goodpasture syndrome - Huser, Martin; Wagnerova, Kristyna; Janku, Petr; Malaskova, Lenka; Stourac, Petr (Gynecologic and obstetric investigation, 2015)
BACKGROUND/AIMS: Goodpasture syndrome (GS) is an autoimmune disease affecting mainly the kidneys and lungs. This review article focuses on GS occurring during pregnancy, which can seriously threaten the lives of both mother and fetus. We summarize the current clinical diagnosis and management of GS in pregnancy. METHODS: A profound literature search was carried out to review all published articles or case studies reporting on GS in pregnancy. We extracted the following data from each case: patient age, parity, gestational age, therapy of GS during pregnancy, pregnancy outcome, neonatal outcome, mode of delivery, and the patient's kidney status. We describe in detail how a recent case of GS diagnosed in pregnancy was successfully treated. RESULTS: A review of the available literature revealed 4 cases of GS in pregnancy. The average patient age was 29.3 ± 2.5 years, and most were primiparous, with an average parity of 1.3 ± 1.5. The average gestational age at the time of diagnosis was 12.5 ± 5.9 weeks. The therapies of GS during pregnancy were remarkably varied. Furthermore, the neonatal outcomes were also quite individual among the observed cases. CONCLUSION: The occurrence of GS during pregnancy is very rare. This unusual pregnancy complication is associated with significant maternal and fetal morbidity. The management of GS during pregnancy requires intensive care and multidisciplinary cooperation.
Keywords: dospělí; Pregnancy Complications; lidé; Female; Pregnancy; antirenální glomerulonefritida; těhotenství; Anti-Glomerular Basement Membrane Disease; komplikace těhotenství; Adult; ženské pohlaví; Humans